NEUROPHYSIOLOGICAL PARAMETERS OF THE VISUAL SYSTEM IN CHILDREN WITH PROGRESSIVE MYOPIA BASED ON THE DATA OF COMPUTER ELECTROENCEPHALOGRAPHY - I. P. Shurygina; M. P. Khadzhieva; I. V. Shlyk; M. K. Shulikova (Кубанский научный медицинский вестник)
This paper addresses the functional state of the cortical visual analyzer in children with progressive myopia based on the results of computer electroencephalography (EEG). We observed 40 patients aged from 7 to 16, including 15 patients with stabilized myopia, 15 patients with progressive myopia, and 10 patients without visual pathologies (the control group). The computer EEG method revealed moderate disruption of the cortico-subcortical interactions with signs of attenuation of the caudal cortical alpha rhythm generator, and enhancement of the functional role of the mast structures in children with a progressive course of myopia.